Interaksi Sosial Umat Baha'i dalam Mempertahankan Identitas Budaya - Hidayat, Samsul; Sulaiman, Sulaiman (Religi: Jurnal Studi Agama-agama, 2024)
This article aims to explore the form of social integration of the Baha'i people in maintaining culture and its contribution to maintaining the cultural identity of religious communities in Kubu Raya, West Kalimantan. This research uses qualitative methods through a sociological-anthropological approach with the type of field study research. Data collection methods in the study using observation, interviews and documentation. Data analysis is done by reducing data, displaying data and drawing conclusions. The results of the study show that the social interaction of the Baha'i people in maintaining cultural identity is shown by the acceptance of the Baha'i people in the community. This is due to cultural integration sourced from Baha'i religious teachings such as unity and peace, cooperation and solidarity and gender equality. In addition, Baha'is play a role in actualizing their culture through joint prayer activities and education, so that the community and Baha'is can interact well in the space. Further studies are needed to look further into the role of Baha'is in human resource development in the community.